KURANGNYA SUMBER DAYA DALAM PROSES KEBIJAKAN PENCATATAN KELAHIRAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN LANDAK - Kunayah E.01109057 (FISIP Universitas Tanjungpura, 2013)
Issues regarding the recording of births that occurred in the Department of Population and Civil Registration of Landak District is existing resources to support the implementation process of birth registration has not been adequately. The inadequacy of the resources in the distribution of citation impact birth certificate to the public. Needs of the community in making a birth certificate is often the time that sudden. Time they use if you want to find a job and continuing education, so employees overwhelmed in handling it. Writing this article aims to determine the adequacy resources on the Departmen of Population and Civil Registration of Landak District in implementation process of birth registration policy. The approach used is descriptive qualitative analysis. The results showed that the implementation of birth registration policy implemented by the Department of Population and Civil Registration of Landak District is quite good, but in terms of implementation there are still shortcomings, such as lack of human resources, budget resources and equipment resources, resulting in delays in distributing quote a birth certificate to the public. Through this writing, that the process of birth registration policy implementation continues, so that people who does nt have a birth certificate in the society can immediately create a birth certificate or in other words to have a birth certificate. Key Words : Birth Registration, Inadequate Resources, Implementation Process Of Birth Registration.